Teaching in the Absence of a Standard Language. A Case Study of Upper Sorbian - Werner, Eduard (Slavia Occidentalis, 2017)
The teaching of Upper Sorbian (USo) is of increasing importance for the survival of this language. A challenge faced by learners is the lack of standardisation. Reliable standardisation has been conducted only in the area of orthography, which offers little indication about pronunciation. Pronunciation, however, is generally missing in all USo dictionaries, and teaching materials offer only general observations. Learners of USo mostly belong to one of two groups which require different teaching strategies: on the one hand, second-language learners aim to achieve authentic pronunciation; native speakers, on the other hand, struggle with the contrast between the standardised etymological orthography and the phonetic representation in everyday language (partly addressed in Šołćina 2014a/b).